Analysis of factors affecting the production of Bagan Boat catches at the Gaung Fish Landing Base (PPI) Padang City, West Sumatra Province - Kurniawan, Feri; Yani, Alit Hindri; Brown, Arthur (South East Asian Marine Sciences Journal, 2024)
The Gaung Fish Landing Base (PPI) is one of the most actively operating sites in Padang City, under the management of the Mina Gates cooperative, and is located in Gaung Market, Lubuk Begalung. Fish production at PPI Gaung comes from the catch of fishing boats that landed at the port: local fishing boats, bagan, tonda, and gillnet. There was a decrease in total fish production landed by 911.42 tons, or a decrease of 33.95% in 2021-2022. This study aims to determine what factors affect the production of catches. The research method used is the survey method, which involves making direct observations in the field and obtaining primary data from interviews with boat-bagan fishermen and secondary data from the port. The results of multiple regression analysis show that all factors have an effect. Six factors have a positive effect, and two have a negative effect. The most influential factor is the length of the trip/sea. The coefficient of determination (R2 ) is 0.757 or 75.7%. The coefficient of determination (R2) of 75.7% means that the presentation of the influence of the independent variables used in the model has an influence of 75.7% on the dependent variable, and the remaining 24.3% is influenced by other variables not included in the model. Other factors that are thought to have an influence include external factors such as the environment, weather, and existing technology. This study concludes that all factors affect the production of catches. Namely, 5 factors have a real influence: engine power, amount of fuel, area of fishing gear, number of lights, and length of trip/sea, while three factors do not significantly affect the size of the ship, the experience of the captain, and the number of crew